MOLEKULYAR FIZIKA VA TERMODINAMIKA ASOSLARIDAN NOSTANDART DARSLARNI MUSOBAQA SHAKLIDA TASHKILLASHTIRISH METODIKASI - Xujanov, E.B.; Baratov, J. (SCIENCE and SOCIETY, 2021)
This article focuses on the use of non-standard tasks in teaching the basics of molecular physics and thermodynamics in general secondary schools and the improvement of teaching methods.